Association of free Tri-iodothyronine Level with Cardiogenic Shock and Prognosis in Patients Hospitalized with Acute STelevation Myocardial Infarction Treated with Streptokinase Therapy (Bangladesh Heart Journal, 2023)
Background: Cardiogenic shock is the leading cause of death in patients with Acute ST-segment Elevation Myocardial Infarction (STEMI). Low free Tri-iodothyronine (FT3) levels are generally associated with poor prognosis in STEMI patients. This study was done to assess the association between FT3 levels and Cardiogenic shock in patients hospitalized with STEMI treated with streptokinase therapy.Methods: This was an observational study of 140 patients of STEMI treated with streptokinase therapy in the department of cardiology, NICVD, Dhaka, Bangladesh from October 2018 to September 2019. The patients were divided into low FT3 (FT3